2020
DOI: 10.1186/s13052-020-00882-9
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric otogenic cerebral venous sinus thrombosis: a case report and a literature review

Abstract: Background: Cerebral venous sinus thrombosis in children is a rare but potentially fatal complication of acute mastoiditis, one of the most common pediatric infectious diseases. Due to its subtle clinical presentation, suspicion is essential for a prompt diagnosis and appropriate management. Unfortunately, no standard treatment options are available. To discuss the possible clinical presentation, microbiology, and management, we here report the case of a child with otogenic cerebral venous sinus thrombosis and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 34 publications
(86 reference statements)
0
8
0
12
Order By: Relevance
“…A 2020 literature review showed that most cases of paediatric otogenic cerebral venous sinus thrombosis have negative bacterial culture tests of the ear exsudate [9]. Although there are some cases of ear infections caused by S.…”
Section: Discussionmentioning
confidence: 99%
“…A 2020 literature review showed that most cases of paediatric otogenic cerebral venous sinus thrombosis have negative bacterial culture tests of the ear exsudate [9]. Although there are some cases of ear infections caused by S.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors recommended anticoagulant therapy for its potential benefits, such as limiting the spread of thrombus, improving sinus recanalization, and reducing sequelae of the nervous system. 4,7,16,17 Ropposch et al 2 treated patients with ordinary heparin for 3 days after surgery, followed by low molecular weight heparin for 3 months, and reported that no complications occurred. 2,3 Coutinho et al 18 treated 16 children with anticoagulation therapy combined with antibiotics and radical mastoidectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the extensive use of antibiotics, the incidence of sigmoid sinus thrombophlebitis has been on the rise in recent years, and symptoms which were considered typical of the disease, such as ''picket fence'' fever, headache, dizziness, nausea, vomiting, neck stiffness, erythema, and altered mental status, with otorrhea, retroauricular edema, and pressing pain (Griesinger sign), [4][5][6][7][8] are no longer typical. The patient did not have typical symptoms of ''picket fence'' fever after admission, owing to his treatment with antibiotics before admission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute mastoiditis is the most frequent AOM complication. More severe complications such as meningitis, subperiosteal, epidural, or intracerebral abscesses may occur albeit uncommon [ 2 ]. Facial nerve paralysis secondary to concurrent AOM is also possible, even if it is rarely reported in children due to the use of broad-spectrum antibiotics, with only 0.005% of patients developing this condition [ 3 ].…”
Section: Introductionmentioning
confidence: 99%